2020
DOI: 10.1038/s41598-020-77805-5
|View full text |Cite
|
Sign up to set email alerts
|

HbWRKY27, a group IIe WRKY transcription factor, positively regulates HbFPS1 expression in Hevea brasiliensis

Abstract: Farnesyl pyrophosphate synthase (FPS) is a key enzyme that catalyzes the formation of farnesyl pyrophosphate, the main initiator for rubber chain initiation in Hevea brasiliensis Muell. Arg. The transcriptional regulatory mechanisms of the FPS gene still not well understood. Here, a WRKY transcription factor designated HbWRKY27 was obtained by screening the latex cDNA library applied the HbFPS1 promoter as bait. HbWRKY27 interacted with the HbFPS1 promoter was further identified by individual Y1H and EMSA assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…HbCZF1 positively regulates the expression of hmg1 , which encodes HMGR ( Guo et al, 2015 ). HblMYB19, HblMYB44, and HbWRKY27 positively regulate the expression of the farnesyl pyrophosphate synthase (FPS) gene HbFPS1 ( Wang et al, 2017 ; Qu et al, 2020 ). HMGR and FPS are key enzymes during natural rubber biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HbCZF1 positively regulates the expression of hmg1 , which encodes HMGR ( Guo et al, 2015 ). HblMYB19, HblMYB44, and HbWRKY27 positively regulate the expression of the farnesyl pyrophosphate synthase (FPS) gene HbFPS1 ( Wang et al, 2017 ; Qu et al, 2020 ). HMGR and FPS are key enzymes during natural rubber biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The reactive oxygen species (ROS) production and ROS-scavenging in laticifers affect latex coagulation ( Zhang et al, 2019b ). In addition, transcription factors are actively implicated in the regulation of latex regeneration ( Wang et al, 2013b ; Li et al, 2016b , 2020a ; Zhang et al, 2019b ; Qu et al, 2020 ). In the present study, DELs acting in the cis-regulation were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agrobacterium tumefaciens GV3101 strains harboring pAsbZIP14-GFP, pAsbZIP41-GFP, or pNC-Cam1304-SubC plasmids were separately grown to OD600 = 0.8 in LB medium at 200 rpm and 28°C and infiltrated into the onion epidermis by Agrobacterium -mediated transformation. The transformed onion epidermis was incubated in darkness at 27°C for 70 h. The GFP fluorescent signal of these onion epidermal cells was monitored using a Leica confocal fluorescence microscope (Wetzlar, Germany) after the nuclei were stained with 20 μg/mL 4´, 6-diamidino-2- phenylindole (DAPI) for 5 min and washed three times with the saline ( Qu et al., 2020 ; Li et al., 2021a ).…”
Section: Methodsmentioning
confidence: 99%
“…HbCZF1 upregulates the expression of hmg1 ( Guo et al, 2015 ). HblMYB19, HblMYB44, and HbWRKY27 upregulated the expression of HbFPS1 ( Wang et al, 2017 ; Qu et al, 2020 ). HbRZFP1 downregulated HRT2 expression ( Guo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%